Autosomal dominant multicore disease. - Vanneste, J A (1982)
Two girls and their mother with multicore myopathy are described. The cores consisted of Z band disorganisation and decreased or absent enzyme activity. Only one case has clinical signs of myopathy. Muscle enzyme activity was elevated in the two children. The mode of inheritance was autosomal dominant.